An asymptotic formula for the generalized stirling numbers of the first kind - Vega, Mary Ann Ritzeil P.; Corcino, Cristina B. (Utilitas Mathematica, 2007)
An asymptotic formula for the generalized Stirling numbers of the first kind Sn,mα,γ is derived for integral values of m in the range h(n) ≤ m ≤ n - O(nδ) where δ is any fixed constant, 0 ≤ 6 ≤ 1, and h(n) is any function such that lim n→∞ h(n) = ∞.